Associations Between Social Determinants and Hypertension, Stage 2 Hypertension, and Controlled Blood Pressure Among Men and Women in the United States - Commodore-Mensah, Yvonne; Turkson-Ocran, Ruth-Alma; Foti, Kathryn; Cooper, Lisa A; Himmelfarb, Cheryl Dennison (American journal of hypertension, 2021)
Social determinants influence the development and control of hypertension. National Health and Nutrition Examination Survey (2011-2018) data for adults aged ≥18 included education, income, employment, race/ethnicity, healthcare access, marital status, and nativity status. Outcomes were hypertension (blood pressure [BP] ≥130/80 mm Hg or self-reported hypertension medication use), stage 2 hypertension (BP ≥140/90 mm Hg), and controlled BP (BP <130/80 mm Hg among those with hypertension). Poisson regression with robust variance estimates was used to examine associations between social determinants and outcomes, by sex. The analysis included 21,664 adults (mean age 47.1 years), of whom 51% were women. After adjustment, hypertension and stage 2 hypertension prevalence remained higher among Black and Asian than White adults, regardless of sex. Blacks had lower prevalence of controlled BP than Whites. Compared with college graduates, men and women with less education had a higher prevalence of hypertension and stage 2 hypertension. Men (prevalence ratio [PR]: 0.28, 95% confidence interval: 0.16-0.49) and women (PR: 0.44, 0.24-0.78) with no routine place for healthcare had lower prevalence of controlled BP than those who had a routine place for healthcare. Uninsured men (PR: 0.66, 0.44-0.99) and women (PR: 0.67, 0.51-0.88) had lower prevalence of controlled BP than those insured. Unemployed or unmarried women were more likely to have controlled BP than employed or married women. Social determinants were independently associated with hypertension outcomes in US adults. Policy interventions are urgently needed to address healthcare access and education, and eliminate racial disparities.